Six Minute Walk Test in People with Tuberculosis Sequelae - Salman Latif, Muhammad Sharyar, Iram Shafee, Jurat Ali, Abdul Mannan, Salman Deedar, Sadaf Waris, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Tuberculosis often brings about diffuse fibrotic and other changes to lung tissue also consolidation of lung tissue prompting a decrease in generally lung tissue compliance. Following tuberculosis, the functional status of people is reduced e.g., impaired ventilation and gas exchanges leading to shortness of breath, muscular deconditioning, and a functional status decline is seen Objective: The purpose of this study was to evaluate and compare the six-meter walk distance and physical functional capacity (VO2 max) in 40 – 65 years people with pulmonary tuberculosis and healthy subjects. Methods: Forty healthy subjects (20 males and 20 females) and forty subjects with pulmonary tuberculosis (30 males and 10 females) took part in this study. All the subjects underwent a six min walk test. Walk-work was calculated and used for evaluating functional capacity. To examine for significant relationships Pearson product correlation was used Results: A significant difference was found between the groups in regards to 6MWT distance (p < 0.05). For height and body mass index (BMI) Pearson product correlations with 6MWD were significant in normal individual and for the weight and BMI it was significant in the TB sequelae group. Conclusion: A significant difference was found in functional capacity in terms of VO2max between healthy and patients with TB was found. TB sequelae individuals’ group, 52.6% patients had a VO2 max under 21 milliliter per kilogram per minute that brought about an impressive effect of TB sequelae on endurance in regards to cardiorespiratory system.